(untitled) (Mūzikas akadēmijas raksti, 2024)
This article considers words and music in close proximity: how ‘words about music’ might occupy themselves in ways other than as ‘mere’ exegesis, and how ‘music about words’ might challenge music’s assumed self-sufficiency. Through examples of my work in ‘creative musicology’, I explore that hinterland where literary-poetic writing borders musicology. An underlying premise of the article is that the products of musical creation are always already ‘critical work done’.